Atrazine persistence applied as commercial and xerogel formulations in oxisol - Trezzi,M.M. (2013)
The intensive use of pesticides have contaminated the soil and groundwater. The application of herbicides as controlled release formulations may reduce the environmental damage related to their use because it may optimize the efficiency of the active ingredient and reducing thus the recommended dose. The objective of this study was to evaluate the persistence of the herbicide atrazine applied as commercial formulation (COM) and as controlled release formulation (xerogel - XER) in Oxisol. The experimental design used was split-plot randomized-blocks with four replications, in a (2 x 6) + 1 arrangement. The two formulations (COM and XER) were assigned to main plots and different atrazine concentrations (0, 3.200, 3.600, 4.200, 5.400 and 8.000 g atrazine ha-1) were assigned to sub-plots. Persistence was determined by means of dissipation kinetics and bioavailability tests. The methodology of bioassays to assess the atrazine availability is efficient and enables to distinguish the tested formulations. The availability of atrazine XER is higher than the commercial in two different periods: up to 5 days after herbicide application and at the 35th day after application. The XER formulation tends to be more persistent in relation to COM formulation.